Strategi Bisnis di Nowly Cafe Medan yang Berdampak pada Keberhasilan Usaha - Manik, Stevanus Wirawan (Innovative: Journal Of Social Science Research, 2025)
The culinary industry, particularly cafés, is one of the food and beverage sectors with a large market share and plays a significant role in contributing to the local economy. This industry has experienced rapid growth in the era of globalization, compelling business actors such as Nowly Cafe in Medan to develop innovative strategies to cope with intense competition and shifting consumer preferences. This study aims to analyze and assess the business strategies implemented by Nowly Cafe Medan and their impact on business success using SWOT analysis. A qualitative approach with a descriptive method was employed to examine the strategies applied by Nowly Cafe and evaluate their effects on growth and profitability amid the competitive culinary industry. The findings indicate that the strategies implemented by Nowly Cafe have made a tangible contribution to business success, as evidenced by an increase in the number of customers, consumer loyalty, and monthly revenue, all of which show a generally positive trend.